Image-Based Position Control for Three-Wheel Omni-Directional Robot - Sri Sukamta; Anan Nugroho; Subiyanto Subiyanto; Rizal Rezianto; Muhammad Febrian Soambaton; Agus Ardiyanto (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2024)
Robotic technology continues to advance, but real-time position tracking of robot movements still faces challenges, especially in dynamic and irregular environments. Sensors often fail to maintain accuracy due to environmental disturbances. This study introduces an innovation using omnidirectional wheels on a three-wheeled robot and image-based position control to improve maneuverability and precision. This method utilizes an infrared camera mounted on the ceiling to detect the robot's position. Image processing algorithms are used to determine waypoints and direct the robot. Omni-directional wheels allow the robot to move freely in all directions, which is important for accurate navigation on complex trajectories. The robot was tested on the "X" and "Square" trajectories in a 1.8-meter x 1.8-meter room to rotate vertical, horizontal, and diagonal movements. The test results showed that on the "X" trajectory, the second movement had the most significant error with a Mean Absolute Error (MAE) of 134.96, while the third movement had the slightest error with an MAE of 52.49, with an average error of 91.36. The first and third movements in the “Square” trajectory showed more significant errors than the second and fourth movements, with MAE of 105.37 and 100.47, respectively. The second and fourth movements had MAE of 67.20 and 59.65, with an average error of 83.17. These results indicate that the image-based control system and omnidirectional wheels improve accuracy compared to conventional methods, which is important for robot navigation applications. Practical implications of this technology include potential applications in the robotics and automation industry. Future research should focus on developing more precise control algorithms and sensors to improve accuracy. Directions for future research include exploring more sophisticated image processing techniques and applying this technology to various industrial scenarios.